Values and leadership styles of managers in Slovenia - Jure Kovač; Manca Jesenko (Journal for East European Management Studies, 2003)
Managers play a key role in the restructuring and transformation of economic structures in transitional countries. It is therefore not surprising that they are at the centre of attention for experts and others as well. This paper describes the results of two studies conducted in 1998 and 2003 regarding the values governing the life, work and leadership styles of managers. Special attention was paid to the shifts in values which occurred in the five-year period between the two studies, and to demonstrating the correlation between an individual's values and his/her leadership style. – – In den Prozessen der Umstrukturierung und Umwandlung der wirtschaftlichen Strukturen in den Reformländern nehmen die Manager eine Schlüsselrolle ein. Es überrascht keineswegs, dass sie im Mittelpunkt des Interesses sowohl der fachlichen als auch einer breiteren Öffentlichkeit stehen. In diesem Beitrag sind die Ergebnisse der 1998 und 2003 durchgeführten Untersuchungen über die Wertorientierung dargestellt, die mit der Lebensführung, der Arbeit, den Unternehmen und Führungsstilen einzelner Manager zusammenhängen. Besonderes Augenmerk wird der Verlagerung der Wertorientierung im besagten Zeitraum von fünf Jahren und der Wechselwirkung der Wertorientierung und der jeweiligen Führungsstile gewidmet.
Keywords: 650; Manager; transitional country; leadership; values; Slovenia